Genetic diversity of Coxiella burnetii in domestic ruminants in central Italy - Di Domenico, M. (BMC Vet Res, 2018)
BACKGROUND: As the epidemiology of human Q Fever generally reflects the spread of Coxiella burnetii in ruminant livestock, molecular characterization of strains is essential to prevent human outbreaks. In this study we report the genetic diversity of C. burnetii in central Italy accomplished by MST and MLVA-6 on biological samples from 20 goat, sheep and cow farms. RESULTS: Five MST and ten MLVA profiles emerged from the analysis establishing a part of C. burnetii strain world atlas. In particular, ST32 occurred on 12 farms (60%), prevalently in goat specimens, while ST12 (25%) was detected on 4 sheep and 1 goat samples. ST8 and a variant of this genotype were described on 2 different sheep farms, whereas ST55 was observed on a goat farm. Five complete MLVA profiles different from any other published genotypes were described in this study in addition to 15 MLVA incomplete panels. Despite this, polymorphic markers Ms23, Ms24 and Ms33 enabled the identification of samples sharing the same MST profile. CONCLUSIONS: Integration of such data in international databases can be of further help in the attempt of building a global phylogeny and epidemiology of Q fever in animals, with a “One Health” perspective.